New Institutionalism in Economics and New Economic Sociology: Main Similarities and the Differences - МаркинМаксим Евгеньевич (Journal of Economic Sociology, 2012)
The article reviews main statements of the influential institutional perspectives, including new institutional economic theory presented by O.Williamson and D. North; new institutionalism in economic sociology developed by organizational theorists (P. DiMaggio, W. Powell, etc.) and sociologists of markets (M. Granovetter, N. Fligstein, etc.) in the USA; and economics of conventions (L. Boltanski and L. Thevenout) in Europe. This analytical review includes a discussion of major similarities and differences of new institutional approaches in economics and sociology.